"Looks Like: the Case of a Victorian Proserpine&#34 - Jukić, Tatjana (Array, 2001)
The text focuses on Dante Gabriel Rossetti's handling of the story of Proserpine and the ways in which it affects the unstable Victorian limits of visuality, realism, myth and autobiography.